Preparation and Performance of Visible‐Light‐Driven Bi2O3/ZnS Heterojunction Functionalized Porous CA Membranes for Effective Degradation of Rhodamine B. Issue 11 (26th March 2018) - Li, Binrong; Chu, Jinyu; Li, Yi; Meng, Minjia; Cui, Yanhua; Li, Qidi; Feng, Yonghai
Abstract : Photocatalytic degradation is an effective method for fast removal of dye‐contaminated water. In the present work, a bismuth oxide/zinc sulfide‐cellulose acetate photocatalytic membrane (Bi2 O3 /ZnS‐CA) is successfully fabricated via the phase‐inversion method with a Bi2 O3 /ZnS heterojunction as the photocatalyst. The Bi2 O3 /ZnS‐CA membranes shows high photocatalytic activity in degradation of Rhodamine B (RhB) under visible‐light irradiation due to the Bi2 O3 /ZnS heterojunction structure contributing to the high efficiency of photogenerated charge separation. The photodegradation efficiency of Bi2 O3 /ZnS‐CA membrane is significantly enhanced (about 30% improvement) and the photodegradation kinetic is four times faster than that of the Bi2 O3 ‐CA and the ZnS‐CA membranes. Moreover, the Bi2 O3 /ZnS‐CA membrane exhibits excellent permeation flux (649.7 L m −2  h −1 ) and high porosity (69.94%). The Bi2 O3 /ZnS‐CA membrane also shows good adsorption performance of RhB, which could enhance the interaction between RhB and the catalyst. This work provides a new sight to construct highly effective visible‐light‐driven photocatalytic membranes for continuous organic dye treatment. Abstract : The visible‐light‐driven Bi2 O3 /ZnS heterojunction is synthesized for the first time and the Bi2 O3 /ZnS‐CA photocatalytic membranes are prepared for the degradation of Rhodamine B (RhB). The RhB molecule is transformed to harmless products by radicals. This work provides a new sight to construct highly effective visible‐light‐driven photocatalytic membranes for continuous organic dye treatment.